The impact of farm credit in Pakistan - Khandker, Shahidur R., 1952- 1952- (Policy research working paper, 2001)
The Agricultural Development Bank of Pakistan (ADBP), which provides most formal loans in Pakistan's rural areas, lends to largeholders far more than to smallholders, although the impact of credit is greater for the smallholders. Targeting credit to smallholders would make ADBP's credit scheme more cost-effective. To reach poor farmers and farmers without assets, in other words to reduce poverty, stringent collateral requirements should be relaxed and outreach should be broadened